Epidemiological, clinical profile and outcome of multi-system inflammatory syndrome in children (MIS-C) admitted in government tertiary care hospital of Kanyakumari district - Samuel, Steeve Gnana; Monikanta, Suresh Placode; Vasudevan, Arul Prasath Subramoniam; Rajamanickam, Nagalekshmi (International Journal of Contemporary Pediatrics, 2021)
We report twelve children with a median age of 7 year (IQR 3years to 12 years) who fulfilled MIS-C WHO criteria. The male to female ratio was 2:1. Affected children had gastrointestinal symptoms (92%), respiratory symptoms (67%), cardiovascular symptoms (58%), neurological symptoms (50%), renal symptoms (33%), followed by muco-cutaneous manifestations (25%). 83% of children had lymphocytopenia. It was found that lymphocytopenia was directly correlated to disease severity. The majority of the children had elevated CRP, transaminase, and deranged coagulation profiles. All 4 systems were involved in 7 children (58%). Intensive care treatment was required for all the cases (100%). There were no deaths. Children with coronavirus disease 2019 (COVID-19) associated MIS-C can present with a wide range of signs and symptoms. They can deteriorate quickly and hence a high index of suspicion; early referral and early initiation of treatment with steroids and IVIg can save the lives of children with MIS-C.